THE ROLE OF PARENTAL MEDIATION AND EMOTIONAL APPEALS IN CHILDREN’S ADVERTISING LITERACY - Chaudhary, Manisha; Singh, Rupam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the digital age, the prevalence of persuasive advertising targeting children has raised critical concerns about their ability to differentiate between entertainment and marketing content. This study investigates the role of parental mediation in enhancing children’s advertising literacy and evaluates the impact of emotional versus rational advertising appeals on brand recall and loyalty. Using a cross-sectional survey of 400 child-parent pairs, the research highlights how active parental involvement, such as discussing media content, significantly improves children’s critical thinking and resistance to advertising. Emotional appeals were found to be more effective in influencing brand recall and loyalty compared to rational appeals, with significant implications for ethical advertising practices. The findings also reveal the challenge children face in recognizing digital ads embedded in interactive content, emphasizing the need for improved media literacy education and regulatory measures. Practical recommendations are offered for parents, educators, and policymakers to better equip children to navigate and critically assess persuasive media messages in an increasingly complex advertising landscape.